Project processes: architectural thought, teaching, andpractice - Fuentes, María Isabel (Artes: Architecture, Technology and Sustainability, 2026)
Architect and urban planner María Isabel Fuentes, a graduate of the Faculty of Architecture at the Catholic University of Santiago de Guayaquil, has developed a distinguished professional and academic career linked to architectural design, construction, and the teaching of architectural design. From the beginning of her professional career, she focused her work on architectural design as the central axis of her production, consolidating, over more than twenty-five years of experience, a continuous process of conceptual, technical, and constructive evolution.